Answer:
j = 38
Explanation:
Solve for j:
7 - j/2 = -12
Put each term in 7 - j/2 over the common denominator 2: 7 - j/2 = 14/2 - j/2:
14/2 - j/2 = -12
14/2 - j/2 = (14 - j)/2:
(14 - j)/2 = -12
Multiply both sides of (14 - j)/2 = -12 by 2:
(2 (14 - j))/2 = -12×2
(2 (14 - j))/2 = 2/2×(14 - j) = 14 - j:
14 - j = -12×2
2 (-12) = -24:
14 - j = -24
Subtract 14 from both sides:
(14 - 14) - j = -14 - 24
14 - 14 = 0:
-j = -14 - 24
-14 - 24 = -38:
-j = -38
Multiply both sides of -j = -38 by -1:
(-j)/(-1) = 38
(-1)/(-1) = 1:
Answer: j = 38